SOCIAL MEDIA STRATEGIES FOR ORGANIZATIONS USING INFLUENCERS’ POWER - Ioanid, Alexandra; Militaru, Gheorghe (European Scientific Journal, ESJ, 2015)
Social media is a big part of our life nowadays and organizations’ managers should use this fact in order to bring their products and services closer to potential customers via online social networks. Social media represents an almost free tool to simulate the word of mouth discussion on a brand, in this way the information getting to customers that would be hard to get to in other ways. The objective of this paper is to analyze the influence certain people can have in social networks and how these social network influence ranks are calculated. Social media is more than just counting likes and shares; it is about taking into consideration all components that might increase the conversion rate. In this paper, there are presented some techniques that might be used to increase the awareness for the brand, creating a powerful community around the brand’s page, raise the interest of potential customers so that in the end, the sales will grow as well. Another important aspect of the influence in social networks, which is analyzed in this paper, refers to the trust that some influencers might use to promote certain brands. This trust was built usually in several years and the influencer has a considerable number of fans on the personal page, so using social media, this large amount of potential customers might be informed about some products or services, considering that with the trust the fans have in the influencer, the conversion rate will be high. The results and conclusions presented in the paper show why managers should take into consideration persons with high social networks influence ranks when planning a marketing campaign for their brands and how online influence might transform into positive business outcome.